Collections care scenario appraisal for painting canvases at Museu Nacional d'Art de Catalunya, Barcelona, Spain. (August 2015) - Oriola, Marta; Campo, Gema; Ruiz-Recasens, Cristina; Pedragosa, Núria; Strlič, Matija
Abstract : We surveyed the canvas of 31 paintings from the collection of the Museu Nacional d'Art de Catalunya, Barcelona, Spain, using non-destructive near infrared spectroscopy (NIR) in order to determine the pH and degree of polymerisation (DP) of the canvas supports. The data showed that the canvases, all from 1890 to 1910, are acidic (average pH 5.1 ± 0.4) and fairly degraded (DP 710 ± 260). Using the dose-response function for cellulosic materials with pH, DP, T, and relative humidity (RH) as inputs, the rate of degradation can be calculated, as well as the period of time until the point when the canvases become so fragile that their handling could lead to mechanical damage and thus risk the integrity of paint layers. On the basis of the survey data, we calculated isochrone plots as well as demographic curves for the collection. Using these, we explored a number of conservation management scenarios and compared them with the expected rate of degradation under current average environmental conditions (21 °C, 58% RH). At these conditions, it is predicted that the average canvas will become fragile and might require interventive treatment in ca. 140 years. However, if the storage temperature is decreased, or if the canvases are deacidified, the period of time until treatment becomes necessary can be considerably increased. As a separate case study we also present a survey of the canvas of The Woman in Hat and Fur Collar (Marie-Thérèse Walter) by Pablo Picasso. The pH and DP of this canvas was determined in 15 sampling points, the averages being pH 5.6 ± 0.2 and DP 1700 ± 320, which allowed us to calculate the isochrone plot for this canvas.